The constructivist approach (coap) to enhance students comprehension in reading procedure text for students of Universitas Muhammadiyah Sidenreng Rappang - Hardianti Hardianti; Jamaluddin Ahmad; Syam Hermansyah (Universitas Ahmad Dahlan)
This research aimed to investigate the constructivist approach to enhance students reading comprehension at UMS Rappang. This research employed the pre-experimental method with one group pre-test and post-test design. The population was the second-year students of UMS Rappang in 2018-2019 academic years. The population included 66 students consisting of three classes; one class (I.2) was taken as a sample by using cluster sampling, as many as 22 students. The instrument used in this research was reading test. The result of this research showed that the pre-test got the mean score of 44.50, while the post-test 64.18. It showed that the p-value (0.000) was lower than the level of significance (alpha (α) = 0.05). It means that H1 was accepted. The research concluded that teaching reading comprehension by using a constructivist approach enhances students’ reading comprehension at the First year of UMS Rappang.